MANAJEMEN MUTU PELAYANAN KESEHATAN PERBANDINGAN SEBELUM DAN SESUDAH AKREDITASI DI POKJA UKP PUSKESMAS SUKAJADI KABUPATEN BANYUASIN (JURNAL SMART ANKES, 2021)
Health development in the 2015-2019 period is the Healthy Indonesia Program with the aim of improving the health status and nutritional status of the community through health and community empowerment efforts supported by financial protection and equitable distribution of health services. The quality of health services is the level of perfection of health services carried out in accordance with the code of ethics and the standard of service determined, thus giving satisfaction to each patient. The aim of the study was to determine the differences in service quality before and after accreditation at the Sukajadi Health Center in Banyuasin Regency. This study was a comparative study and used paired t-test with a total of 96 respondents. The results showed that there was a difference between tangible, reability, responsiveness, assurance and empathy with the quality of services before and after accreditation. The most dominant variable influencing service quality before accreditation is assurance (p-value: 0,001), and the most dominant vari1able influencing service quality after accreditation is the empirical variable (p-value: 0,00). It is expected that the increase in the quality of services after accreditation will increase the number of visits of patients who come for treatment and the quality of service in the health center is getting better quality.